2020
DOI: 10.1039/c9ra10462c
|View full text |Cite
|
Sign up to set email alerts
|

Resonant energy transfer and light scattering enhancement of plasmonic random lasers embedded with silver nanoplates

Abstract: The resonant energy transfer enhancement from a plasmonic random laser has been investigated by means of a dye-covered PVA film embedded with silver nanoplates with different sizes and morphologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…According to the results, we understand that the bird feather consists of keratin, one structural protein, which tolerates less exciting energy than chitin, the main material of butterfly wings 34 . However, the threshold of this framework is competitive with the metallic nanoparticles embedded in polymers 21 .
Figure 5 ( a ) Emission spectra of S0 with 2.3 μJ (green) and 4.9 μJ (red) pump energy for different exposure times.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results, we understand that the bird feather consists of keratin, one structural protein, which tolerates less exciting energy than chitin, the main material of butterfly wings 34 . However, the threshold of this framework is competitive with the metallic nanoparticles embedded in polymers 21 .
Figure 5 ( a ) Emission spectra of S0 with 2.3 μJ (green) and 4.9 μJ (red) pump energy for different exposure times.
…”
Section: Resultsmentioning
confidence: 99%
“…Weng et al studied that adding a patterned sapphire substrate efficiently reduced the lasing threshold from 2.55 to 0.15 μJ in CH 3 NH 3 PbBr 3 perovskite thin films 18 . Hsiao et al tuned the resonant energy transfer by different sizes of silver nanoparticles, and the threshold of random lasers from the dye-doped polymer is manipulated from 15.75 to 1.12 μJ 21 . Wan et al reported plasmonic titanium nitride (TiN) nanoparticles enhanced low-threshold random lasing from dye-doped nematic liquid crystals 22 , the laser threshold decreases from 6.13 to 2.37 μJ/pulse when the number density of TiN nanoparticles increases from 5.613 × 10 10 /ml to 5.314 × 10 11 /ml.…”
Section: Introductionmentioning
confidence: 99%
“…2 By means of their broad emission bandwidth, structural tunability and large stimulated emission cross section, organic laser dyes have played a vital role in the development of ultrafast lasers and have been recognized as promising gain media in emerging laser systems. To date, many commercially available laser dyes such as rhodamine 6G (R6G), pyrromethene 597 (PM597) and dichloromethane (DCM) 3 have been adopted as active media to produce random lasers (RLs) in cooperation with nanostructure materials such as liquid crystals, 4 TiO 2 , 5 polymers 6,7 and electro-spun fiber. 8 In contrast to conventional lasers with cavity mirrors, the generated photons of RLs can be efficiently trapped in a disordered nano-structure by recurrent light scattering to form a number of closed loops.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer composites not only limit their arms to sensors and energy generators, but they also govern breakthroughs in fields such as light-emitting diodes (LEDs), lasers, solar cells, field effect transistors, memory devices, and soft robots [12][13][14]. For instance, polymeric composite light emissive layers empower the efficiency and stability of the LEDs [15,16].…”
Section: Introductionmentioning
confidence: 99%